Analysis and optimisation of window layers for thin film CDTE solar cells - Francesco Bittau (2017)
The work presented in this thesis focuses on the investigation and improvement of the window stack of layers for thin film CdTe solar cells fabricated in the Center for Renewable Energy Systems Technology (CREST) laboratories. In particular the aim was to change the standard structure including TCO, high resistive transparent (HRT)layer and CdS which is limited by the low transparency of the CdS layer, to a better performing one. The first result chapter of the thesis describes the study of ZnO HRT layers. ZnO thin films were deposited by radio frequency (RF) magnetron sputtering with different structural, optical and electrical properties which were characterized by X-ray diffraction, electron microscopy, spectrophotometry, Hall Effect method and 4-point probe. ZnO films were then incorporated in CdTe solar cells with the structure: FTO/ZnO/CdS/CdTe/Au back contact and the performance of these devices were compared with the film properties to single out trends and identify optimal film characteristics. By varying the deposition pressure of ZnO films, it was possible to increase their transparency and significantly increase their resistivity. While better transparency positively affected the solar cell current density output and efficiency, the resistivity of ZnO films did not show any clear impact on device efficiency. By increasing the deposition temperature the ZnO film grain size was increased. Increased FF was observed in devices incorporating ZnO layers with bigger grains, although this gain was partially counterbalanced by the Voc degradation, leading to a limited efficiency improvement. Finally the addition of oxygen had the main effect of increasing the resistivity of ZnO films, similarly to what happened with the increase of the sputtering pressure. In this case however, an improvement of FF, Jsc and efficiency was observed, especially at an O2/Ar ratio of 1%. By simulating the solar cells behavior with SCAPS-1D, it was found that these performance change can be explained by the variation of interface properties, precisely the amount of interface defects, rather than by bulk properties. The study presented in the second result chapter focuses on magnesium-doped zinc oxide (MZO) and the variation of its energy band structure. MZO was initially used as the HRT layer within a solar cell structure: FTO/MZO/CdS/CdTe/Au back contact. Sputtering MZO films with a target containing MgO 11 weight% and ZnO 89 weight% allowed for and increased band gap from 3.3 eV of intrinsic ZnO to 3.65 eV for MZO deposited at room temperature. Increasing the superstrate deposition temperature allowed for a further band gap increase up to 3.95 eV at 400 °C due mainly to an conduction band minimum upward shift. It was highlighted the importance to create a positive conduction band offset with the MZO layer conduction band slightly above the CdS conduction band, with an optimum found in this case to be 0.3 eV (efficiency 10.6 %). By creating a positive conduction band offset all the performance parameters (Voc, FF, Jsc, efficiency) significantly increased. One of the reasons for this improvement was found to be a diminished interface recombination due to a more ideal MZO/CdS band alignment. In the second part of this investigation the MZO was used as a replacement for the CdS in a simplified structure: FTO/MZO/CdTe/Au back contact. The concepts used to optimise the performance of these devices also involved tuning the conduction band alignment between MZO/CdTe and efficiencies of 12.5 % were achieved with a at conduction band offset. The efficiency increase was achieved mainly thanks to a better transparency of the MZO layer and a higher Jsc output, compared to devices using a CdS buffer layer. The MZO buffers have been tested in combination with different TCOs. Results are presented in the third result chapter and showed that AZO is a good alternative to FTO working effectively in combination with MZO. AZO/MZO efficiency thin film CdTe solar cells (12.6%, compared to 12.5% with FTO). It was found that increasing the IR transparency of the TCOs leads to a potentially higher Jsc. Achieving a better transparency was obtained by using TCOs with high mobility and lower carrier concentration (AZO and ITiO) and also by using a boro-aluminosilicate glass with low iron content. ITiO yielded the best opto-electrical properties among all the TCO materials. Devices incorporating ITiO however, showed lower performance then those using FTO and AZO. ITO/MZO windows also yielded poor performance. In addition, the ITO films deposited had a high carrier concentration leading to a high NIR absorption by plasma resonance and resulted not ideal for application in thin film CdTe PV.